Verifiable and Nonverifiable Information in a Two-Period Agency Problem - Jörg Budde (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
I examine how a firm's opportunity to verify information influences the joint use of verifiable and unverifiable information for incentive contracting. I employ a simple two-period agency model, in which contract frictions arise from limited liability and the potential unverifiability of the principal's information about the agent's action. With short-term contract, the principal benefits from both a more informative and a more conservative verification of his private information. With long-term contracts, he may prefer a less informative verification, but his preference for a conservative verification persists.
urn:nbn:de:bvb:19-epub-17412-9
Keywords: 330